The impact of agency problems on M&A performance in emerging markets - Yap, Kha Ying (2022)
Merger and acquisition (M&A) is a method for firms to expand their organisation more rapidly than organically and a conduit for firms to expand their worldwide market position and increase competitiveness. M&A activity has expanded quickly in the 21st century, particularly in emerging countries. However, studies show that the acquiring firms did not achieve financial gain or even experienced loss post-M&A. Researchers indicate agency problems is a primary issue of corporate governance and remain a prominent issue in emerging markets that affect the M&A performance of the acquiring firms. Agency problems is divided into two categories: (1) divergence of interest between the shareholders and managers (principal-agent conflict); and (2) expropriation of minority shareholders (principal-principal conflict). The concentrated ownership structure of emerging market firms may alleviate principal-agent conflict. However, it is questionable whether mitigation of principal-agent conflict improves the M&A performance due to the presence of two sets of principals, majority shareholders and dispersed shareholders may result in principal-principal conflict.